1998
DOI: 10.1126/science.281.5374.246
|View full text |Cite
|
Sign up to set email alerts
|

A Reduction-Pyrolysis-Catalysis Synthesis of Diamond

Abstract: Diamond powder was synthesized through a metallic reduction-pyrolysis-catalysis route with the reaction of carbon tetrachloride and sodium at 700 degreesC, in which the sodium was used as reductant and flux. This temperature is much lower than that of traditional methods. The x-ray powder diffraction patterns showed three strong peaks of diamond. The Raman spectrum showed a sharp peak at 1332 inverse centimeters, which is characteristic of diamond. Although the yield was only 2 percent, this method is a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(57 citation statements)
references
References 22 publications
0
56
0
1
Order By: Relevance
“…Further, KSHV genome copies were dependent on the expression of survivin and the modification of histone acetylation. Previous studies have shown that survivin has different levels of expression during cell cycle phases in cancer cells (69,70). Therefore, we postulated that the expression of LANA, AK-B, and survivin may have an impact on KSHV genome copies in a cell cycle-dependent manner.…”
Section: Resultsmentioning
confidence: 93%
“…Further, KSHV genome copies were dependent on the expression of survivin and the modification of histone acetylation. Previous studies have shown that survivin has different levels of expression during cell cycle phases in cancer cells (69,70). Therefore, we postulated that the expression of LANA, AK-B, and survivin may have an impact on KSHV genome copies in a cell cycle-dependent manner.…”
Section: Resultsmentioning
confidence: 93%
“…В частно-сти, при температуре 300°C был получен кристалл нитрида галлия размером 30 нм. Группа иссле-дователей так же создала экономически эффек-тивный метод каталитического пиролиза алмаз-ного порошка [7]. Посредством реакции, локали-зованной в нанотрубке, группа исследователей из Университета Цинхуа создала "одномерную" нанопроволоку нитрида галлия, которая имеет диаметр от 4 до 50 нм и длину до 25 мм [8].…”
Section: получение наноматериаловunclassified
“…Employing a Wurtz-type reaction coupling alkyl halides with excess metal sodium as both reductant and flux, fine carbon powders containing a trace amount of diamond (yield @ 2%) ( Figure 7.14(c)) were synthesized via a reduction-pyrolysis-catalysis route by reacting CCl 4 with metallic sodium at 700 C [53]. This temperature is much lower than that of traditional methods.…”
Section: Synthesis Of Diamond Carbon Nanotubes and Carbidesmentioning
confidence: 99%